2021
DOI: 10.1080/02656736.2021.1983036
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 inhibition acts synergistically with heat to induce a pro-immunogenic form of cell death in colon cancer cells

Abstract: Background: Sub-ablative heat induces pleiotropic biological effects in cancer cells, activating programmed cell death or survival processes. These processes decide the fate of the heated cell. This study investigates these and assesses whether heat, in combination with HSP90 inhibition, augments cell death and induces a pro-immune phenotype in these cells. Methods: HCT116 and HT29 cells were subjected to thermal doses (TID) of 60 and 120CEM 43 using a PCR thermal cycler. HSP90 was inhibited with NVP-AUY922. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 82 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…Combined with HSP90 inhibition, thermal doses led to synergistic decreases in cell viability and the induction of apoptosis, along with increased Calreticulin exposure, CD47 downregulation, and HSP70 release. These findings suggest that sub-ablative heating, in combination with HSP90 inhibition, can promote a pro-immunogenic form of cell death in colon cancer cells [78]. Some research studies evaluated the immunological response triggered by HIFU treatment in mice with colon adenocarcinoma tumors.…”
Section: Emerging Trends In High-intensity Focused Ultrasound Researc...mentioning
confidence: 99%
“…Combined with HSP90 inhibition, thermal doses led to synergistic decreases in cell viability and the induction of apoptosis, along with increased Calreticulin exposure, CD47 downregulation, and HSP70 release. These findings suggest that sub-ablative heating, in combination with HSP90 inhibition, can promote a pro-immunogenic form of cell death in colon cancer cells [78]. Some research studies evaluated the immunological response triggered by HIFU treatment in mice with colon adenocarcinoma tumors.…”
Section: Emerging Trends In High-intensity Focused Ultrasound Researc...mentioning
confidence: 99%
“…When focused ultrasound is applied in its continuous "thermal" mode (exposures lasting seconds), the tissue is subjected to frictional forces which are converted to heat [74]. Hyperthermia treatments (characterised by temperatures of 43-45 • C maintained for up to an hour) have been used to sensitise tumours to the effects of radiotherapy and chemotherapy [75][76][77][78][79][80][81][82][83][84][85][86][87]. At higher power, high-intensity focused ultrasound (HIFU) heats cells rapidly, to temperatures over 56 • C for a few seconds, resulting in thermal necrosis and instantaneous cell death.…”
Section: Therapeutic Focused Ultrasoundmentioning
confidence: 99%
“…Cancers 2022, 14, x FOR PEER REVIEW 4 of 25 temperatures of 43-45 °C maintained for up to an hour) have been used to sensitise tumours to the effects of radiotherapy and chemotherapy [75][76][77][78][79][80][81][82][83][84][85][86][87]. At higher power, highintensity focused ultrasound (HIFU) heats cells rapidly, to temperatures over 56 °C for a few seconds, resulting in thermal necrosis and instantaneous cell death.…”
Section: Therapeutic Focused Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…This, along with increased antigen expression, can help recruit more T-cells to attack the tumor cells, resulting in a stronger antitumor immune response . This response has been observed to not only eliminate the primary tumor but also distant untreated metastatic tumors, known as the abscopal effect . A study by Huang et al has reported that HSP90 inhibition acts synergistically with subablative heat induced by the PCR thermal cycler to induce a pro-immunogenic form of cell death by increased calreticulin exposure on the plasma membrane, downregulation of CD47, and release of HSP70 in colon cancer cells grown as monolayers post-96 h of treatment .…”
Section: Introductionmentioning
confidence: 99%